Pathogenicity of Salmonella: A Literature Study - Widhie Estiningtyas; Ima Arum Lestarini; Nikita Andini Putri; Diajeng Aesya Mutiara Firdausy (Jurnal Biologi Tropis, 2026)
Salmonella is a type of gram-negative bacteria that belongs to the Enterobacteriaceae family and is a major health issue worldwide because it can lead to different illnesses in both humans and animals. This comprehensive study explores the pathogenicity of Salmonella, focusing on its general characteristics, mechanisms of pathogenesis, and host-pathogen interactions. The research examines the taxonomy, morphology, and biochemical properties of Salmonella, highlighting the diversity within the genus and its adaptability to various environments. The study then delves into the complex mechanisms of pathogenicity, including adhesion to host cells, tissue invasion, intracellular survival, and modulation of host immune responses. Particular focus is placed on the significance of Salmonella Pathogenicity Islands (SPIs) and the Type III Secretion Systems (T3SS) they code for in relation to virulence. In addition, the research examines how the host's immune system reacts to a Salmonella infection, covering both innate and adaptive immune responses. This study also looks into the clinical symptoms associated with Salmonella infections, which can vary from mild gastroenteritis that resolves on its own to serious systemic illnesses such as typhoid fever. Diagnostic methods, including traditional culture techniques and modern molecular approaches, are evaluated for their efficacy in detecting and characterizing Salmonella infections. Finally, the study examines current prevention and treatment strategies, including vaccination and antibiotic therapy, while addressing the growing concern of antimicrobial resistance. This comprehensive analysis of Salmonella pathogenicity provides valuable insights into the intricate host-pathogen relationship and highlights potential avenues for developing novel therapeutic and preventive strategies against Salmonella infections.